(untitled) (Journal of Naval Architecture and Marine Engineering, 2016)
This paper deals with the heat and mass transfer in unsteady flow of Powell-Eyring fluid past an inclined stretching sheet in the presence of radiation, non-uniform heat source/sink and chemical reaction with suction/injection effects. The governing equations are reduced into system of ordinary differential equations using similarity transformation and solved numerically using Runge-Kutta based shooting technique. Results display the influence of governing parameters on the flow, heat and mass transfer, friction factor, local Nusselt and Sherwood numbers. Comparisons are made with the existed studies. Present results have an excellent agreement with the existed studies. Results indicate that an increase in the chemical reaction parameter depreciates the friction factor, heat transfer rate and enhances the mass transfer rate. Dual solutions exist only for certain range of suction/injection parameters.